2019
DOI: 10.5771/2509-9485-2019-2-343
|View full text |Cite
|
Sign up to set email alerts
|

Diskriminierungs- und Rassismuserfahrungen geflüchteter Menschen in Deutschland: Ein Forschungsüberblick

Abstract: Auf Grundlage einer Systematisierung des bisherigen Forschungsstands werden in diesem Beitrag einerseits Lebensbereiche definiert, in denen Geflüchtete von Diskriminierung und Rassismus betroffen sind. Andererseits werden konkrete Diskriminierungs- und Rassismusformen sowie -ausprägungen aufgezeigt. Die Befunde belegen, dass geflüchtete Menschen in Deutschland in nahezu allen Lebensbereichen individuell bzw. institutionell Diskriminierung und Rassismus erfahren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Aksoy et al (2020) have convincingly demonstrated that negative attitudes toward migrants influence refugees' economic integration negatively. Furthermore, discrimination refugees might experience in the access to employment, housing and in everyday interaction might slow down their economic progress in the host country (Montgomery and Foldspang, 2008;Foroutan et al, 2017;Diekmann and Fereidooni, 2019). Whereas survey-based research and in-depth interviews capture self-reports of refugees' experiences with racism and labor market discrimination (Pichl, 2017;Diekmann and Fereidooni, 2019;Röder et al, 2021), experimental research is likely to directly quantify the extent of discriminatory behavior on the part of employers.…”
Section: Social Distances and Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aksoy et al (2020) have convincingly demonstrated that negative attitudes toward migrants influence refugees' economic integration negatively. Furthermore, discrimination refugees might experience in the access to employment, housing and in everyday interaction might slow down their economic progress in the host country (Montgomery and Foldspang, 2008;Foroutan et al, 2017;Diekmann and Fereidooni, 2019). Whereas survey-based research and in-depth interviews capture self-reports of refugees' experiences with racism and labor market discrimination (Pichl, 2017;Diekmann and Fereidooni, 2019;Röder et al, 2021), experimental research is likely to directly quantify the extent of discriminatory behavior on the part of employers.…”
Section: Social Distances and Discriminationmentioning
confidence: 99%
“…Furthermore, discrimination refugees might experience in the access to employment, housing and in everyday interaction might slow down their economic progress in the host country (Montgomery and Foldspang, 2008;Foroutan et al, 2017;Diekmann and Fereidooni, 2019). Whereas survey-based research and in-depth interviews capture self-reports of refugees' experiences with racism and labor market discrimination (Pichl, 2017;Diekmann and Fereidooni, 2019;Röder et al, 2021), experimental research is likely to directly quantify the extent of discriminatory behavior on the part of employers. In a series of correspondence tests, Arai et al (2016) uncovered discrimination against job applicants with Arabicsounding names in the Swedish context, with men being particularly affected.…”
Section: Social Distances and Discriminationmentioning
confidence: 99%
“…have convincingly demonstrated that negative attitudes toward migrants influence refugees' economic integration negatively. Furthermore, discrimination refugees might experience in the access to employment, housing and in everyday interaction might slow down their economic progress in the host country (Montgomery and Foldspang, 2008;Foroutan et al, 2017;Diekmann and Fereidooni, 2019). Whereas survey-based research and in-depth interviews capture self-reports of refugees' experiences with racism and labor market discrimination (Pichl, 2017;Diekmann and Fereidooni, 2019;Röder et al, 2021), experimental research is likely to directly quantify the extent of discriminatory behavior on the part of employers.…”
Section: Social Distances and Discriminationmentioning
confidence: 99%
“…Furthermore, discrimination refugees might experience in the access to employment, housing and in everyday interaction might slow down their economic progress in the host country (Montgomery and Foldspang, 2008;Foroutan et al, 2017;Diekmann and Fereidooni, 2019). Whereas survey-based research and in-depth interviews capture self-reports of refugees' experiences with racism and labor market discrimination (Pichl, 2017;Diekmann and Fereidooni, 2019;Röder et al, 2021), experimental research is likely to directly quantify the extent of discriminatory behavior on the part of employers. In a series of correspondence tests, Arai et al (2016) uncovered discrimination against job applicants with Arabicsounding names in the Swedish context, with men being particularly affected.…”
Section: Social Distances and Discriminationmentioning
confidence: 99%
“…The issue is increasingly being addressed by politicians, the media, social media and in research. While most people focus on examining either the prevalence of ethnic discrimination and racism (attitudes, discourses, actions) and the individual or institutional causes, there is still a gap to be filled in regard to the dynamics and mechanisms of ethnic discrimination in everyday situations-such as encounters in the neighborhood (Diekmann and Fereidooni, 2019). During such encounters, it is likely that several causes affect how, for example neighbors, will react toward one another.…”
Section: Introductionmentioning
confidence: 99%